IMPROVING THE STRATEGY FOR FIGHTING AGAINST THE ECONOMIC CRISIS IN SMALL BUSINESS ENTITIES (Scientific journal of the Fergana State University, 2024)
In this article, the reforms carried out in the process of improving the strategy of combating the economic crisis in small business entities, in particular, the further development of production and social infrastructure, the effective use of the natural and economic potential of the republicʼs regions, new work in improving the strategy of combating the economic crisis of small business entities in Uzbekistan It has been analyzed in detail that targeted measures have been developed for the formation and localization of production.